Circulating tumor cells as a preoperative risk marker for occult metastases in patients with resectable cholangiocarcinoma - Fründt, Thorben; von Felden, Johann; Krause, Jenny; Heumann, Asmus; Li, Jun; Riethdorf, Sabine; Pantel, Klaus; Huber, Samuel; Lohse, Ansgar W.; Wege, Henning; Schulze, Kornelius (Frontiers in Oncology, 2022)
Cholangiocarcinoma (CCA) is an aggressive tumor associated with a high rate of recurrence after resection. An important risk factor for recurrence is the presence of occult metasta-ses, which are not radiologically detectable at the time of diagnosis. There are currently no biomarkers for the preoperative assessment of micrometastases. A previous study demonstrated the prognostic relevance of circulating tumor cells (CTC) in patients with advanced CCA but the potential of CTCs as a preoperative marker for detecting occult metastases has not been investigated so far. In this two-phase study, we first recruited a cohort of 27 patients with histologically proven, metastatic CCA or gallbladder cancer (GBCA) to assess feasibility (feasibility cohort, FC). CTCs were measured in the peripheral blood using the CellSearch System (CSS) between October 2012 and January 2017. Subsequently, in 11 patients undergoing curative-intended resection for CCA (intrahepatic CCA: n =4; extrahepatic CCA n= 6; gallbladder cancer: n=1), peripheral and central venous blood specimens were obtained to improve detection rate by simultaneous measurement and to elucidate distribution of CTCs in different venous compartments. Presence of CTCs detection was correlated with postoperative TNM-status. In the FC, CTCs (range 1-3 cells, median: 1) were detected in 40% (11/27) patients and were signifi-cantly associated with worse overall survival (hazard ratio: 3.59; 95% CI: 1.79- 7.1; p = 0.04). By combined peripheral and central measurement, CTC detection was increased to 54% (6/11) in the resection cohort (RC) and was associated with metastases that were only identified during the surgical procedure (peritoneal carcinoma: n = 1; infiltration of the duodenum: n = 1) or immediately after surgery (evidence of pulmonary metastases by CT scan two days after resection, not evident on initial tumor staging prior resection). Taken together, in this single center pilot study, we demonstrated that CTCs are detectable in CCA patients and are associated with significantly impaired survival in patients at metastatic stage. Detection rate prior to surgery was improved to >50% by combined peripheral and central measurement. Moreover, preoperative CTC detection may indicate existing metastases and could help to stratify patients more accurately.